The impact of economic partnership agreements on ACP agriculture imports and welfare - Oliver Morrissey; Evious Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
This paper estimates the impact on a sample of 36 ACP countries of eliminating tariffs on agricultural imports from the EU under EPAs, considering trade, welfare and revenue effects. Even assuming `immediate' complete elimination of all tariffs on agriculture imports from the EU, and when excluding up to 20% of imports as sensitive products, over half of ACP countries are likely to experience welfare gains. However, although most LDCs gain (10 out of 13), most non-LDCs (about 60%) lose. The overall welfare effect relative to GDP tends to be very small, whether positive or negative. While potential tariff revenue losses are nonnegligible, given that countries have at least ten years in which to implement the tariff reductions, there is scope for tax substitution. An important issue is identifying the sensitive products (SPs) to be excluded. In general, excluding SPs reduced the welfare gain (or increased the welfare loss) compared to estimates where no products are excluded.
Keywords: F14; F15; F17; 330; EU-ACP; Economic Partnership Agreements; ACP Agriculture Imports; Handelsabkommen; Agraraußenhandel; Wohlfahrtsanalyse; AKP-Staaten; EU-Staaten